Hepatitis B virus and its sexually transmitted infection – an update - Takako Inoue; Yasuhito Tanaka (Microbial Cell)
Epidemiology, incidence and prevalence: About 5% of the world’s population has chronic hepatitis B virus (HBV) infection, and nearly 25% of carriers develop chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC). The prevalence of chronic HBV infection in human immunodeficiency virus (HIV)-infected individuals is 5%-15%; HIV/HBV coinfected individuals have a higher level of HBV replication, with higher rates of chronicity, reactivation, occult infection, and HCC than individuals with HBV only. The prevalence of HBV genotype A is significantly higher among men who have sex with men (MSM), compared with the rest of the population. Molecular mechanisms of infection, pathology, and symptomatology: HBV replication begins with entry into the hepatocyte. Sodium taurocholate cotransporting polypeptide was identified in 2012 as the entry receptor of HBV. Although chronic hepatitis B develops slowly, HIV/HBV coinfected individuals show more rapid progression to cirrhosis and HCC. Transmission and protection: The most common sources of HBV infection are body fluids. Hepatitis B (HB) vaccination is recommended for all children and adolescents, and all unvaccinated adults at risk for HBV infection (sexually active individuals such as MSM, individuals with occupational risk, and immunosuppressed individuals). Although HB vaccination can prevent clinical infections (hepatitis), it cannot prevent 100% of subclinical infections. Treatment and curability: The goal of treatment is reducing the risk of complications (cirrhosis and HCC). Pegylated interferon alfa and nucleos(t)ide analogues (NAs) are the current treatments for chronic HBV infection. NAs have improved the outcomes of patients with cirrhosis and HCC, and decreased the incidence of acute liver failure.